2019
DOI: 10.1111/pedi.12960
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure and carotid intima media thickness in children with type 1 diabetes

Abstract: Background/Objective: Blood pressure abnormalities may play an important role in macrovascular damage in type 1 diabetes. Little is known about blood pressure abnormalities and macrovascular damage in children with type 1 diabetes.Methods: Children with type 1 diabetes (n = 57) for a short (3 months-2 years; n = 24) or long duration (≥5 years; n = 33) and a group of control children without diabetes (n = 29) completed 24-h ambulatory blood pressure monitoring (ABPM).Carotid intima media thickness (cIMT), a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 47 publications
(61 reference statements)
1
3
0
1
Order By: Relevance
“…Similar to our results Dost et al found elevated daytime SBP and nighttime SBP and DBP compared with the historic controls (23). The high prevalence of ABP abnormalities in T1D children including 24-hour, daytime and nighttime SBP, DBP and mean arterial BP indices was also observed in recently published smaller Canadian study (24).…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 92%
“…Similar to our results Dost et al found elevated daytime SBP and nighttime SBP and DBP compared with the historic controls (23). The high prevalence of ABP abnormalities in T1D children including 24-hour, daytime and nighttime SBP, DBP and mean arterial BP indices was also observed in recently published smaller Canadian study (24).…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 92%
“…Masked hypertension in T1D patients is associated with longer duration of T1D, higher insulin requirement, and unstable glycemia [ 53 ••]. Isolated nocturnal hypertension, a subtype of MH, was a predictor of carotid intima media thickness, another sign of hypertension-mediated organ damage (HMOD) [ 54 ]. Lurbe et al confirmed an association of the increase in nocturnal systolic BP and development of albuminuria during the follow-up [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our meta-analysis has demonstrated that T1DM children are strongly associated with endothelial dysfunction. It should be noted that previous studies have proved that other arterial abnormalities were demonstrated in children with T1DM, 5457 which indicate the need for strict monitoring of cardiovascular disease risk factors and/or subclinical signs of atherosclerosis in children with T1DM. Also, higher LDL-C levels may potentially contribute to endothelial dysfunction in T1DM children.…”
Section: Discussionmentioning
confidence: 96%